Analisis Sistem Dan Prosedur Akuntansi Pembayaran Gaji Dan Upah Pada PT Palma Asia Lestari Mandiri Di Kecamatan Sepaku Kabupaten Penajam Paser Utara - Rinata Yuni Astuti; Irwansyah Irwansyah; Ibnu Abni Lahaya (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2018)
The objective of this thesis is to know the implementation of system and accountancy procedure toward the salary payment of salary the employess at PT. Palma Asia Lestari Mandiri in Kecamatan Sepaku based on the elements of internal control. This research used comprasion method in which comparing the system and procedure of payment accountancy implemented by the company with the system and procedure in accordance to present theories. The results of this research is PT. Palma Asia Lestari Mandiri in Kecamatan Sepaku North Penajam Paser regency still not sufficient because it has not applied the elements of internal control based on the present theories